Affective and psychotic process triggered by methylphenidate - Yarıcı, Umut; Görgülü, Yasemin; Köse Çınar, Rugül (Journal of Dependence, 2017)
Methylphenidate is used in treating patient with attention deficit hyperactivity disorder in adults and children (ADHD), narcolepsy, depression augmentation treatment, cancer pains. It is known that methylphenidate can cause manic and psychotic symptoms at high doses, even in small groups, at therapeutic doses. In this case report we present two patients, who had no previous psychiatric outpatient clinic application or psychiatric treatment history, with psychotic manic episode and psychotic depressive episode accompanied by catatonia due to the application of methylphenidateafterthediagnosisofADHD.